Assessment of Complete Remission Rate in Patients with Acute Myeloid Leukemia Undergoing 7+3 Induction Chemotherapy: Remission Rates in Acute Myeloid Leukemia Patients - Mehboob, Nazish; Khan, Asma; Munir, Attiya; Tahir, Muhammad; Ali, Amanat; Ahmed, Sameer (Pakistan Journal of Health Sciences, 2024)
Acute leukemia is a fast-growing, overpopulated clone of immature proliferating cells that largely predominate in the bone marrow and have the capacity to prolong life indefinitely. Upon inspection and cytologic assessment of bone marrow or peripheral blood, the cells demonstrate quantified uncertainties. Objective: To determine the frequency of complete remission after induction 7+3 chemotherapy in patients with acute myeloid leukemia. Methods: The nature of this study was cross sectional study at Department of Oncology, Pakistan Institute of Medical Sciences, and Islamabad from 26 November, 2022 to 26 May, 2023. The hospital’s laboratory fulfilled the complete blood count and provided the confirmed baseline bone marrow biopsy reports. All patients who were admitted received treatment with a 7+3 regime, a standard treatment protocol for all the adolescents and adults admitted. Every patient was prescribed for 7+3 induction therapy regimen which consists of 200 mg/m2 cytarabine for seven days and idarubicin for three days, 12 mg/m2 on the 1st, 3rd and 5th day. Results: The complete remission estimated turns out to be 61.1% and rest need further treatment. The average age of the patients was 48.56 ± 6.91 years. The mean BMI stood at 24.46 ± 1.49 kg/m2. gender wise, 74 were male and 21 were female. Our mean CR was 61.1% that is 58 participants all the complete demographic is available. Conclusions: This study revealed a Complete Remission (CR) rate of 61.1% in patients with AML undergoing 7+3 induction chemotherapy. However, our findings suggest that older age is associated with lower CR rates, highlighting the need for tailored treatment strategies that balance efficacy with the potential risks of intensive therapies in this population.